THE EFFECT OF PRODUCT QUALITY, BRAND IMAGE AND CONSUMER SATISFACTION ON CONSUMER LOYALTY XIAOMI SMARTPHONES IN LHOKSUKON CITY COMMUNITY - Muhammad Nasrol; T.Edyansyah; Siti Maimunah; Sapna Biby (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This study aims to examine and analyze the effect of product quality, brand image, and consumer satisfaction on consumer loyalty Xiaomi smartphone in Lhoksukon City Community, North Aceh District. The research method used is quantitative method and the sampling technique is Incidental Sampling, then the data collection technique uses a questionnaire using a Likert scale. The results of the study explain that in the Product Quality variable (X1) Partially Product Quality has a positive and significant effect on Consumer Loyalty (Y) with ho rejected and Ha accepted, then on the Brand Image variable (X2) Brand Image has a partially positive and significant effect on Consumer Loyalty (Y) with Ho rejected and Ha accepted , then on the Consumer Satisfaction variable (X3 ) Consumer Satisfaction has a positive and significant effect on Consumer Loyalty (Y) with ho rejected and Ha accepted , then simultaneously Product Quality (X1), Brand Image (X2), and Consumer Satisfaction (X3) have a positive and significant effect on Consumer Loyalty (Y) in the Lhoksukon City Community.